Effectiveness of a Commercial Lactic Acid Bacteria Intervention Applied to Inhibit Shiga Toxin-Producing Escherichia coli on Refrigerated Vacuum-Aged Beef - Katie R. Kirsch; Tamra N. Tolen; Jessica C. Hudson; Alejandro Castillo; Davey Griffin; T. Matthew Taylor (International Journal of Food Science)
Because of their antagonistic activity towards pathogenic and spoilage bacteria, some members of the lactic acid bacteria (LAB) have been evaluated for use as food biopreservatives. The objectives of this study were to assess the antimicrobial utility of a commercial LAB intervention against O157 and non-O157 Shiga-toxigenic E. coli (STEC) on intact beef strip loins during refrigerated vacuum aging and determine intervention efficacy as a function of mode of intervention application. Prerigor strip loins were inoculated with a cocktail (8.9±0.1 log10 CFU/ml) of rifampicin-resistant (100.0 μg/ml; RifR) O157 and non-O157 STEC. Inoculated loins were chilled to ≤4°C and treated with 8.7±0.1 log10 CFU/ml LAB intervention using either a pressurized tank air sprayer (conventional application) or air-assisted electrostatic sprayer (ESS). Surviving STEC were enumerated on tryptic soy agar supplemented with 100.0 μg/ml rifampicin (TSAR) to determine STEC inhibition as a function of intervention application method (conventional, ESS) and refrigerated aging period (14, 28 days). Intervention application reduced STEC by 0.4 log10 CFU/cm2 (p<0.05), although application method did not impact STEC reductions (p>0.05). Data indicate that the LAB biopreservative may assist beef safety protection when utilized within a multi-intervention beef harvest, fabrication, and aging process.